On the notions of taxonomic 'impediment', 'gap', 'inflation' and 'anarchy', and their effects on the field of conservation. Issue 3 (19th April 2021) - Raposo, Marcos A.; Kirwan, Guy M.; Lourenço, Ana Carolina Calijorne; Sobral, Gisela; Bockmann, Flávio Alicino; Stopiglia, Renata
Abstract : (Received 14 June 2019; accepted 23 September 2020) We examine notions of taxonomic 'impediment', 'gap', 'inflation' and 'anarchy', all of which are increasingly prevalent in discussions of the global biodiversity crisis. Following a critical analysis of the history of those notions, we postulate that the entire issue behind them resides in a deep philosophical deficiency in the general comprehension of taxonomic principles. In particular, there is a profound "conceptual turbulence" in the knowledge flux between taxonomy and conservation biology. In general, taxonomists only vaguely understand what conservationists wish to preserve, and conservationists appear to not consider more profound taxonomic issues and the consequences for their interests. Thereafter, we demonstrate the importance of constructing a more solid theoretical bridge between these disciplines, as well as the importance of refining concepts surrounding diversity estimates and species extinction in a world where knowledge can be considered to be increasingly fluid. We also underline the importance of constantly reflecting on the targets of conservation action and strategy, especially the urgency of the question regarding the species as the main unit to be preserved. Ultimately, for taxonomists, it is important to embrace philosophy to make theoretical knowledge more consistent with the wealth of biological theory and empirical data currently at our disposal. Especially, we stress that without a straightforward theoretical dialogue between the delimitation methods and conceptual frameworks such as those governing operational formulae (e.g., DNA barcoding, or reciprocally monophyletic populations), the resultant species should not be viewed as necessarily comparable, or be considered as of equal utility to all fields of investigation, including conservation.